Experimental and Numerical Analysis of a Plate Heat Exchanger Using Variable Heat Transfer Coefficient. Issue 18 (26th July 2022) - Jamil, Muhammad Ahmad; Goraya, Talha S.; Yaqoob, Haseeb; Shahzad, Muhammad Wakil; Zubair, Syed M.
Abstract: Thermal design and analysis of heat exchangers are predominantly conducted considering constant heat transfer coefficients. However, these vary along the length and affect the calculations of heat transfer rates and area allocations. The current paper investigates the variations in the heat transfer coefficients in plate heat exchangers (PHX), using different numerical approaches. The heat transfer coefficient is calculated at the inlet, outlet, and systematically selected intermediate points for each method. The analysis is conducted for two different systems, i.e., a laboratory-scale and an industrial scale PHX at different chevron angles. It is concluded that the effect of the variable heat transfer coefficient is more significant for the large-scale heat exchanger due to high flow rates, geometrical specifications, Reynolds number, and thermophysical properties. The deviation of the local heat transfer coefficient along the heat exchanger length is approximately 9–14% and 3–6% for industrial and laboratory scale PHX, while an area deviation of around 15% is observed.